2014
DOI: 10.21829/abm107.2014.204
|View full text |Cite
|
Sign up to set email alerts
|

Cambios estacionales en conjuntos de dinoflagelados epifíticos cerca de la costa norte de la Península de Yucatán, Golfo de México

Abstract: Epiphytic dinoflagellates were studied in 250 samples from 10 sites in Chelem (a semi-enclosed mangrove lagoon) and Dzilam de Bravo (an exposed coastal locality), on the northern coast of the Yucatan Peninsula, during five surveys in [2008][2009]. Temperature, salinity, turbidity, pH, dissolved oxygen, nitrates, nitrites, phosphates, silicates, urea, extractable water column chlorophyll-a, precipitation, and wind speed and direction were measured. The Chelem lagoon system showed minor variability in physical-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…As consequence, the taxonomic composition of epiphytic dinoflagellates cannot be unequivocally determined by using the standard methodology (rough morphometric discrimination), and for purposes of practicality and comparability it is necessary to work with this "schematic" community. The taxonomic composition of the epiphytic dinoflagellate community on the surveyed algae of this study is quite similar to those reported in similar studies in the Caribbean (Morton and Faust, 1997;Delgado et al, 2006;Boisnoir et al, 2018) and other regions of the North Atlantic like the south of the Gulf of Mexico (Okolodkov et al, 2007(Okolodkov et al, , 2014 or Florida (Bomber et al, 1989) and even in the Pacific (Parsons and Preskitt, 2007;Richlen and Lobel, 2011) although each species (or genus) did not contribute in the same proportion to the total abundance. For example, Delgado et al (2006) found that P. lima and G. toxicus were more abundant than O. lenticularis and C. monotis, whereas Boisnoir et al (2018) reported that Ostreopsis spp.…”
Section: Taxonomic Composition Of Epiphytic Dinoflagellatessupporting
confidence: 89%
See 2 more Smart Citations
“…As consequence, the taxonomic composition of epiphytic dinoflagellates cannot be unequivocally determined by using the standard methodology (rough morphometric discrimination), and for purposes of practicality and comparability it is necessary to work with this "schematic" community. The taxonomic composition of the epiphytic dinoflagellate community on the surveyed algae of this study is quite similar to those reported in similar studies in the Caribbean (Morton and Faust, 1997;Delgado et al, 2006;Boisnoir et al, 2018) and other regions of the North Atlantic like the south of the Gulf of Mexico (Okolodkov et al, 2007(Okolodkov et al, , 2014 or Florida (Bomber et al, 1989) and even in the Pacific (Parsons and Preskitt, 2007;Richlen and Lobel, 2011) although each species (or genus) did not contribute in the same proportion to the total abundance. For example, Delgado et al (2006) found that P. lima and G. toxicus were more abundant than O. lenticularis and C. monotis, whereas Boisnoir et al (2018) reported that Ostreopsis spp.…”
Section: Taxonomic Composition Of Epiphytic Dinoflagellatessupporting
confidence: 89%
“…were numerically more abundant than Coolia and Gambierdiscus. In the Gulf of Mexico, Okolodkov et al (2007) found that depending of the site and the date P. lima or C. monotis could dominate the community, and in the Yucatan coast, Prorocentrum species, particularly P. rathymum was the dominant species on seagrass meadows present in Yucatan coast (Okolodkov et al, 2014).…”
Section: Taxonomic Composition Of Epiphytic Dinoflagellatesmentioning
confidence: 99%
See 1 more Smart Citation
“…-Beltrán et al, 1998;Núñez-Vázquez et al, 2000;Cortés-Lara et al, 2005;Núñez-Vázquez, 2005;Okolodkov and Gárate-Lizárraga, 2006;Gárate-Lizárraga et al, 2007;Gárate-Lizárraga, 2012;Morquecho-Escamilla et al, 2016, 2017Gallegos-Mendiola et al, 2017;Sepúlveda-Villarraga et al, 2017;Gárate-Lizárraga et al, 2018 El Delgado et al, 2002;Delgado-Miranda, 2005;Moreira-González et al, 2016 Puerto Rico Gambierdiscus G. toxicus (?) Ostreopsis O. lenticularis Tosteson et al, 1986 Bahamas Coolia C. santacroce Dominican Republic Coolia C. palmyrensis C. malayensis British and United States Virgin Islands Coolia C. santacroce C. malayensis Carlson and Tindall, 1985;Litaker et al, 2009;Rains and Parsons, 2015 (Continued) Faust, 1990aFaust, ,b, 1993cFaust, ,d, 1994Faust, , 1995Faust, , 1996Faust, , 1997Faust, , 1999Faust, , 2000Faust, , 2004Faust and Gulledge, 1996;Morton and Faust, 1997;Faust and Steidinger, 1998;Faust et al, 2008;Litaker et al, 2009 Okolodkov et al, 2007Okolodkov et al, , 2009Barón-Campis et al, 2014;Okolodkov et al, 2014;Martínez-Cruz et al, 2016;Estrada-Var...…”
Section: Eastern Pacific Coast Of Latin Americamentioning
confidence: 99%
“…lima, and P. rhathymum were found in a reef zone at Chachalacas, Veracruz (Estrada-Vargas et al, 2017). In 2008-2009, seasonal changes were followed at ten sampling sites in the Chelem lagoon system and in the area exposed to the open sea at Dzilam de Bravo in the coast of Yucatan (Okolodkov et al, 2014). Prorocentrum lima and P. rhathymum were the most abundant species among 20 dinoflagellate taxa identified and associated with four seagrass and 33 macroalgal species.…”
Section: Gulf Of Mexicomentioning
confidence: 99%